2008
DOI: 10.1002/ajmg.b.30746
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of parkinsonism, rigidity, rest tremor, and bradykinesia in African‐Caribbean inpatients: Differences in association with dopamine and serotonin receptors

Abstract: We studied the association between polymorphisms of genes coding for dopamine D(2) (DRD2), dopamine D(3) (DRD3), serotonin 2(a) (HTR2A), and serotonin 2(c) (HTR2C) receptors and Antipsychotic-Induced Parkinsonism (AIP), rigidity, bradykinesia, and rest-tremor in African-Caribbeans treated with antipsychotics. Polymorphisms of DRD2 (-141CIns/Del, TaqIA, 957C > T), DRD3 (Ser9Gly), HTR2A (-1438A > G, 102T > C, His452Tyr), and HTR2C (-759C > T, Cys23Ser) genes were determined according to standard protocols. The U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Correction for the possible effects of these SNPs is indicated in our study, because these SNPs have been associated with AIP, rigidity, and bradykinesia in the same African-Caribbean sample (Al Hadithy et al, 2008). There were no differences in age or in the utilization patterns of antipsychotics, anticholinergics, and benzodiazepines and the lack of association is therefore not likely to be caused by these potential confounders.…”
Section: Demographic and Clinical Features Of The Subjectsmentioning
confidence: 63%
See 1 more Smart Citation
“…Correction for the possible effects of these SNPs is indicated in our study, because these SNPs have been associated with AIP, rigidity, and bradykinesia in the same African-Caribbean sample (Al Hadithy et al, 2008). There were no differences in age or in the utilization patterns of antipsychotics, anticholinergics, and benzodiazepines and the lack of association is therefore not likely to be caused by these potential confounders.…”
Section: Demographic and Clinical Features Of The Subjectsmentioning
confidence: 63%
“…Several risk factors have been suggested to predispose to AIP such as old age, female gender, high antipsychotic dose, and hereditary predisposition (Al Hadithy et al, 2008;Caligiuri et al, 1999;Hirose, 2006;Jabs et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Five studies so far have reported associations with acute antipsychotic-induced MD without specifying the MD under study (Al-Janabi et al 2009;Greenbaum et al 2007Greenbaum et al , 2009Gunes et al 2007Gunes et al , 2008. To our knowledge, only one candidate study has reported significant results with akathisia specifically (Eichhammer et al 2000) and only one with parkinsonism (Al Hadithy et al 2008) both in an older sample with a mean age of 40 and 49 years, respectively. The affinities for multiple receptors of second-generation antipsychotics, other than the prevailing affinity for the DRD2 receptor of the first-generation antipsychotics, may be responsible for the differing pharmacogenetic associations found in our group of patients.…”
Section: Discussionmentioning
confidence: 80%
“…The reported association between functional DRD2 promoter allele −141C Del and tardive dyskinesia was not found previously (de Leon et al 2005;Hori et al 2001; Kaiser et al 2002;Zai et al 2007) but an association was found between this promoter allele and antipsychotic-induced parkinsonism (Al Hadithy et al 2008). This may be of clinical interest as antipsychotic-induced parkinsonism has been shown to be a risk factor for the development of tardive dyskinesia (Kane 2006;Tenback et al 2006Tenback et al , 2009.…”
Section: Discussionmentioning
confidence: 95%
“…Cardiovascular ranked second with Puerto Rico [25][26][27][62][63][64] and Costa Rica [11,15,16,50,60,65,113] as the main contributors. Neurology/psychiatry placed third with a greater contribution of the Caribbean islands of Curaçao [85,86,110], Martinique [87], Jamaica [56,61], Cuba [82] and Puerto Rico [35,36,66,95] (Figure 3). These results are in agreement with the global trend of scientific research in these areas [10].…”
Section: Pharmacogenetic Research In Central America and The Caribbean mentioning
confidence: 99%